Disability and Gender: Analyzing the Double Disadvantage in Education and Employment - Hussein, Hussein (The Center for Disability Studies and Services Brawijaya University, 2025)
This article explores the intersection of disability and gender, analyzing the compounded disadvantages individuals with disabilities face in education and employment contexts. Drawing from a wide range of academic sources, including feminist disability studies and labor market research, the paper examines how gender and disability intersect to create unique barriers for women and men with disabilities. The research highlights the structural inequalities in both education and employment that limit access to opportunities, focusing particularly on the African context. By analyzing these factors through a gendered disability lens, the study advocates for inclusive policies and practices that address both the challenges of gender and disability simultaneously.